N-Phenyl-6-(1H-pyrazol-1-yl)pyridazin-3-amine - Ather, Abdul Qayyum (International Union of Crystallography, 2010)
The molecule of title compound, C(13)H(11)N(5), is essentially planar (r.m.s. deviation = 0.0440 Å) and an intramolecular C—H⋯N hydrogen bond generates an S(6) motif. In the crystal, molecules are connected into chains by intermolecular N—H⋯N and C—H⋯N hydrogen bonds. In addition, π–π stacking interactions are observed between the pyrazole and pyridazine rings [interplanar distance = 3.6859 (10) Å].